Improving energy efficiency at palm oil mill industries - Noranai, Zamri; Mohd Joharudin, Nurul Farahin; Redzwan, Muhammad Aliff Asyraf; Abdul Latif, Noradila; Hassan, Nur Zaha (2021)
Palm oil production has become one of the essential economical in Malaysia, where it is one of the world's largest oil palm producer and exporter. The rapid growth of the palm oil mill as the primary product dominating Malaysian agriculture industries leads to the increasing of energy usage. However, the efficiency of electrical energy usage has been recognized as one of the significant factors to reduce the cost of electrical energy consumption. This research aims to determine the energy consumption of palm oil mill process and proposed improvement to its potential energy consumption. This research is limited to the energy efficiency improvement in one of Malaysia palm oil industry. The palm oil mill selection and the palm oil mill processes have been identifying in the early phases. Four main palm oil processes which are fruit bunch reception, sterilizing, threshing and pressing have been investigating to improve the energy efficiency. From the calculation of processing palm oil processes, the monthly electrical consumption was near to 127MWh. The result found that 31.49% of energy consumption can be reduced in a month by the selected palm oil mill processes by replacing the current motor to high-efficiency motor.